Pengaruh Bentuk Impeller pada Proses Koagulasi Flokulasi Terhadap Pola Aliran dan Penyisihan TSS - Komang Mega Ilda Utari; Mohamad Mirwan (Yayasan Literasi Sains Indonesia, 2023)
Environmental pollution caused by wastewater has reached alarming levels, especially in large cities like Surabaya, where household wastewater is a major contributor. The coagulation-flocculation method is used to treat wastewater by precipitating particles from the wastewater. The use of mechanical impellers plays a crucial role in this process. This study analyzes the influence of impeller design, mixing time, and impeller rotation speed on the efficiency of Total Suspended Solid (TSS) removal and flow patterns in coagulation-flocculation. An impeller with a blade angle of 30° produces a wider and more effective flow pattern compared to a 60° angle. The number of blades and the blade angle affect TSS removal efficiency, with a 6-blade impeller at 30° angle achieving the highest efficiency. The optimal mixing time is 1 minute for coagulation and 20 minutes for flocculation. The optimal impeller rotation speed is 100 rpm for coagulation and 60 rpm for flocculation. The findings provide practical guidelines for enhancing the efficiency of domestic wastewater treatment.